2012
DOI: 10.1021/la3020173
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Subgel-Phase Formation Using an Asymmetric Phospholipid Bilayer Membrane by High-Pressure Fluorometry

Abstract: The myristoylpalmitoylphosphatidylcholine (MPPC) bilayer membrane shows a complicated temperature-pressure phase diagram. The large portion of the lamellar gel (L(β)'), ripple gel (P(β)'), and pressure-induced gel (L(β)I) phases exist as metastable phases due to the extremely stable subgel (L(c)) phase. The stable L(c) phase enables us to examine the properties of the L(c) phase. The phases of the MPPC bilayers under atmospheric and high pressures were studied by small-angle neutron scattering (SANS) and fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…On the other hand, considerably large values and the acyl chain-length dependence of the H and V values cannot be explained by only the hydration change near the head group. Recently, we have found [54] that bilayers of some asymmetric PCs with different linear acyl chains in length are suitable for a study of the L c phase formation because they form the L c phase in a much shorter time than CnPCs, and because the formation is further accelerated by the application of pressure. Our previous high-pressure fluorometric study on a myristoylpalmitoylphosphatidylcholine bilayer suggested that the asymmetric PC molecules in the L c phase are probably arranged in staggered structure where polar head groups of the molecules are alternately protruding with respect to the membrane surface.…”
Section: Comparison Of Bilayer Phase Transitions Among the Homologs Omentioning
confidence: 99%
“…On the other hand, considerably large values and the acyl chain-length dependence of the H and V values cannot be explained by only the hydration change near the head group. Recently, we have found [54] that bilayers of some asymmetric PCs with different linear acyl chains in length are suitable for a study of the L c phase formation because they form the L c phase in a much shorter time than CnPCs, and because the formation is further accelerated by the application of pressure. Our previous high-pressure fluorometric study on a myristoylpalmitoylphosphatidylcholine bilayer suggested that the asymmetric PC molecules in the L c phase are probably arranged in staggered structure where polar head groups of the molecules are alternately protruding with respect to the membrane surface.…”
Section: Comparison Of Bilayer Phase Transitions Among the Homologs Omentioning
confidence: 99%
“…In general, it is well known that the L c phase formation of the bilayers of symmetric PCs with saturated acyl chains is very slow [26] and the formation requires a thermal treatment called annealing before experiments. On the other hand, the MPPC and PMPC can form the L c phase easily on account of the metastability of the L β ′ phase, in particular, the L c phase formation of the MPPC bilayer is very fast and the fast formation enables us to study the state of the L c phase in detail by a method of high-pressure fluorometry [38]. Moreover, there is a two-phase coexistence region (gray-colored area in the figure) of the L β ′ and L β I phases in the SPPC bilayer.…”
Section: Effect Of Acyl Chain Structure On the Phase Behavior Of Pmentioning
confidence: 99%